Divestiture, Corporate Performance And Ownership Expropriation: Evidence On Malaysia Public-Listed Companies - Ung, Likjing; Rayenda Khresna, Brahmana; Puah, Chin Hong; Hooy, Chee-Wooi (Varazdin Development and Entrepreneurship Agency (VADEA), 2016)
This paper investigates the impact of divestiture strategy on Malaysia listed company performance. This paper attempts to determine ownership expropriation and use of proceeds associated based on the Agency Theory. We consider a sample of more than 100 companies between 2008 and 2013. We focus on Malaysia listed firm which is developing country. Our findings provide that return on asset as accounting measures performance will tend to increase when divestiture strategy is adopted while Tobin’s q as market-based measures performance will decrease when divestiture strategy is used by firm.